Definition of Public Servants (Colonial Letters and the Contact of Knowledges, 1935)
This file contains colonial memorandum on the definition of civil servants
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies